Insights to improve the activity of glycosyl phosphorylases from Ruminococcus albus 8 with cello-oligosaccharides - Storani, Alem; Guerrero, Sergio A.; Iglesias, Alberto A. (Frontiers in Chemistry, 2023)
The phosphorolysis of cello-oligosaccharides is a critical process played in the rumen by Ruminococcus albus to degrade cellulose. Cellodextrins, made up of a few glucosyl units, have gained lots of interest by their potential applications. Here, we characterized a cellobiose phosphorylase (RalCBP) and a cellodextrin phosphorylase (RalCDP) from R. albus 8. This latter was further analyzed in detail by constructing a truncated mutant (Ral∆N63CDP) lacking the N-terminal domain and a chimeric protein by fusing a CBM (RalCDP-CBM37). RalCBP showed a typical behavior with high activity on cellobiose. Instead, RalCDP extended its activity to longer soluble or insoluble cello-oligosaccharides. The catalytic efficiency of RalCDP was higher with cellotetraose and cellopentaose as substrates for both reaction directions. Concerning properties of Ral∆N63CDP, results support roles for the N terminal domain in the conformation of the homo-dimer and conferring the enzyme the capacity to catalyze the phosphorolytic reaction. This mutant exhibited reduced affinity toward phosphate and increased to glucose-1-phosphate. Further, the CBM37 module showed functionality when fused to RalCDP, as RalCDP-CBM37 exhibited an enhanced ability to use insoluble cellulosic substrates. Data obtained from this enzyme’s binding parameters to cellulosic polysaccharides agree with the kinetic results. Besides, studies of synthesis and phosphorolysis of cello-saccharides at long-time reactions served to identify the utility of these enzymes. While RalCDP produces a mixture of cello-oligosaccharides (from cellotriose to longer oligosaccharides), the impaired phosphorolytic activity makes Ral∆N63CDP lead mainly toward the synthesis of cellotetraose. On the other hand, RalCDP-CBM37 remarks on the utility of obtaining glucose-1-phosphate from cellulosic compounds.